Comparison Between Free-Choice and No-Choice Seedling Bulk Tests for Evaluating Resistance of Rice Cultivars to the Whitebacked Planthopper - Saxena, R.C.; Khan, Z.R. (Wiley, 1984)
During a screening of rice, Oryza sativa L., cultivars for resistance to the whitebacked planthopper Sogatella furcifera (Horváth) by the routinely used free‐choice seedling bulk test, a significantly higher insect population was observed to move over to the susceptible check cultivar soon after infestation. This uneven distribution of insects caused unbalanced infestation among the test cultivars. To avoid this shortcoming, a no‐choice seedling bulk test was conducted in which each row of test cultivar seedlings was excluded from the other by an intervening, vertical, mylar plastic partition, and was exposed to equal insect infestation. The resistance scores of 10 genetically diverse cultivars—‘Muskhan 41’ (Wbph 1), ‘N22’ (Wbph 1), ‘N32’ (Wbph 1), ‘ARC 10239’ (Wbph 2), ‘ADR 52’ (Wbph 3), ‘Podiwi A8’ (wbph 4), ‘Colombo’ (Wbph 2 + 1 recessive ?), ‘WC 1240’ (Wbph I + 1 recessive ?), ‘1R 2035‐117‐3’ (Wbph 1 + Wbph 2), and ‘Taichung Native 1’ (no resistance gene)—from free‐choice and no‐choice seedling bulk tests were compared. Podiwi A8 and N22, rated as moderately resistant and resistant in the free‐choice test, proved to be susceptible and moderately resistant, respectively, in the no‐choice test.The no‐choice test ensures an even distribution of test insects on cultivars and excludes any possibility of their escape from infestation. The technique has important implications in screening for resistance against a number of mobile insect pest species on a wide variety of plants.